Exchange rate volatility, financial constraints and trade: empirical evidence from Chinese firms - Jérôme Héricourt; Sandra Poncet (FIW - Research Centre International Economics, 2013)
This paper studies how firm-level export performance is affected by Real Exchange Rate (RER) volatility and investigates whether this effect depends on existing financial constraints. Our empirical analysis relies on export data for more than 100,000 Chinese exporters over the period 2000-2006. We confirm a trade-deterring effect of RER volatility. We find that the value exported by firms, as well as their probability of entering new export markets, decrease for destinations with higher exchange rate volatility and that this effect is magnified for financially vulnerable firms. As expected, financial development does seem to dampen this negative impact, especially on the intensive margin of export. These results provide microfounded evidence that financial constraints may play a key role in determining the macro impact of RER volatility on real outcomes.
Keywords: F1; F31; L25; 330; Exchange rate volatility; financial development; exports